Ziria: Wireless Programming for Hardware Dummies - Stewart, Gordon; Gowda, Mahanth; Mainland, Geoffrey; Radunovic, Bozidar; Vytiniotis, Dimitrios (2013)
Software-defined radio (SDR) brings the flexibility of software to the domain of wireless protocol design, promising both an ideal platform for research and innovation and the rapid deployment of new protocols on existing hardware. However, existing SDR platforms either require careful hand-tuning of low-level code, negating many of the advantages of software, or are too slow to be useful in the real world. In this paper we present Ziria, the first software-defined radio platform that is both easily programmable and performant. Ziria introduces a novel programming model tailored to wireless physical layer tasks and captures the inherent and important distinction between data and control paths in this domain. We describe an optimizing compiler for Ziria, provide a detailed evaluation, and give a line-rate Ziria implementation of 802.11a/g.